The Concept of Carrying Capacity in Tourism - Josef Zelenka; Jaroslav Kacetl (Amfiteatru Economic)
Carrying capacity is often pragmatically, theoretically as well as purely intuitively considered as a concept in the context of tourism sustainability. The carrying capacity application has the greatest potential in protected areas, in frequently visited cultural and natural attractions, and in relation to sustaining of the lifestyle of the local community and tourism destination potential in general. Despite its importance, partial applications, determination of basic theoretical principles, and specifying connection to the other theoretical concepts in tourism (particularly destination life cycle, LAC concept, visitors management), there still is a rightful opinion of some authors suggesting that there is no consistent theory of tourism carrying capacity. This theory would be the base for sophisticated practical carrying capacity applications. This paper is therefore focused on introduction of the theoretical concept of carrying capacity, which can be discussed and possibly further elaborated.